ANALISIS PENGARUH PARAMETER PROSES PEMBUBUTAN TERHADAP HARGA KEKASARAN MENGGUNAKAN METODE TAGUCHI - Mohammad Rafi (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
ABSTRACT The minimum level of precision is the goal to be achieved during the process of turning bends using a CNC lathe. In this case, a simpler permutation rate will result in a good permutation rate (smaller is better). a slow process will affect how long it takes the product to take care of and increase production costs. To work around this, a parameter setting procedure is needed that produces the least surface roughness of the workpiece. This study tries to identify the elements that affect the surface roughness of the CNC lathe process, as well as the combination of factors (feed speed, spindle rotation, and feed depth) to the minimum surface roughness. The Taguchi method and the L9 (3^3) orthogonal matrix were used in the research procedure. because there are three layers for the three process parameters. The repetition was done twice. The results of the study were used to calculate the surface roughness value. the levels of the process parameters of spindle rotation (put/min), feeding and depth of cut that can create surface roughness. The results of this study indicate the right combination of parameter variables to produce surface roughness with a minimum feed depth of 0.8 mm, and a feed motion of 0.3 mm/rev and a rotation of 2213 rpm.